Vestibular evoked myogenic potentials using low frequency stimuli - Oliveira, Aline Cabral de (2011)
Vestibular evoked myogenic potentials are vestibulocervical reflexes resulting from sacculus stimulation with strong intensity sounds. Normality parameters are necessary for young normal individuals, using low frequency stimuli, which configure the most sensitive region of this sensory organ. AIM: To establish vestibular evoked myogenic potential standards for low frequency stimulation. MATERIAL AND METHOD: Vestibular evoked myogenic potential was captured from 160 ears, in the ipsilateral sternocleidomastoid muscle, using 200 averaged tone-burst stimuli, at 250 Hz, with an intensity of 95 dB NAn. CASE STUDY: Clinical observational cross-sectional. RESULTS: Neither the student's t-test nor the Mann-Whitney test showed a significant difference in latency or vestibular evoked myogenic potential amplitudes, for p <; 0.05. Irrespective of gender, we found latencies of p13-n23 and p13-n23 interpeaks of 13.84 ms (± 1.41), 23.81 ms (±1.99) and 10.62 ms (± 6.56), respectively. Observed values for amplitude asymmetry between the ears were equal to 13.48% for females and 3.81% for males. CONCLUSION: Low frequency stimuli generate vestibular evoked myogenic potentials, with adequate morphology and amplitude, thereby enabling the establishment of standard values for normal individuals at this frequency.